Preservation of Local Traditions through Cultural Tourism: A Case Study of Traditional Villages in Indonesia - Benowo, Yusril; Uekita, Yuki; Wang, Liang (Tourism and Hospitality Research, 2026)
Cultural tourism has become a strategic instrument for preserving local traditions amid rapid globalization and socio-cultural transformation. Traditional villages in Indonesia represent living cultural landscapes where customs, rituals, architecture, and local wisdom continue to evolve alongside tourism development. This study aims to analyze how cultural tourism contributes to the preservation of local traditions in Indonesian traditional villages while identifying strategies that balance cultural continuity and tourism sustainability. Employing a qualitative descriptive approach, this research synthesizes findings from multiple case studies across Indonesia, including Sade, Penglipuran, Kemiren, Cireundeu, Pedawa, and other traditional villages documented in recent scholarly literature. Data were collected through systematic literature analysis of peer-reviewed journals indexed nationally and internationally and were analyzed using thematic content analysis. The results indicate that cultural tourism plays a dual role: it strengthens cultural resilience through ritual revitalization, community participation, and intergenerational knowledge transfer, while simultaneously posing risks of commodification and cultural simplification. However, community-based tourism, local wisdom integration, and customary governance mechanisms significantly mitigate these risks. This study concludes that cultural tourism can serve as an effective tool for preserving local traditions when managed through participatory, culturally sensitive, and sustainability-oriented frameworks. The findings contribute to the discourse on sustainable cultural tourism and offer practical insights for policymakers, local communities, and tourism planners.